2014
DOI: 10.1177/0192623314549960
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Environmental Chemicals Associated with the Development of Toxicant-associated Fatty Liver Disease in Rodents

Abstract: Background Toxicant associated fatty liver disease (TAFLD) is a recently identified form of non-alcoholic fatty liver disease (NAFLD) associated with exposure to industrial chemicals and environmental pollutants. Numerous studies have been conducted to test the association between industrial chemicals/ environmental pollutants and fatty liver disease both in vivo and in vitro. Objectives The objective of the paper is to report a list of chemicals associated with TAFLD. Methods Two federal databases of rode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
97
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3
2

Relationship

1
9

Authors

Journals

citations
Cited by 134 publications
(103 citation statements)
references
References 35 publications
2
97
0
4
Order By: Relevance
“…In utero and lactational exposure to BPA in a rat model demonstrated a reduction in hepatic glycogen content at 21 weeks of age with evidence that the promoter for hepatic glucokinase was hypermethylated, suggesting a reduction in the expression of this key enzyme [537]. In a multigenerational rat model, BPA exposure in the F0 generation promoted glucose intolerance and insulin resistance in the F2 generation with an associated reduction in hepatic glucokinase expression and concomitant hypermethylation of the gene promoter [547]. Interestingly, adult mice exposed to BPA have also been shown to exhibit reduced hepatic glucokinase activity [548].…”
Section: Mdcs and Metabolism-relevant Diseasesmentioning
confidence: 99%
“…In utero and lactational exposure to BPA in a rat model demonstrated a reduction in hepatic glycogen content at 21 weeks of age with evidence that the promoter for hepatic glucokinase was hypermethylated, suggesting a reduction in the expression of this key enzyme [537]. In a multigenerational rat model, BPA exposure in the F0 generation promoted glucose intolerance and insulin resistance in the F2 generation with an associated reduction in hepatic glucokinase expression and concomitant hypermethylation of the gene promoter [547]. Interestingly, adult mice exposed to BPA have also been shown to exhibit reduced hepatic glucokinase activity [548].…”
Section: Mdcs and Metabolism-relevant Diseasesmentioning
confidence: 99%
“…Hundreds of millions of people worldwide have liver diseases, which are one of the prominent reasons of morbidity and mortality (33). A number of environmental toxicants, chemicals, and drugs can cause se-rious cellular injuries in various organs of the body by metabolic activation (34). CCL 4 is one of the environmental chemicals that cause hepatic injuries.…”
Section: Discussionmentioning
confidence: 99%
“…A study of Al-Eryani et al (2015) identified 123 chemicals associated with fatty liver. Pesticides and their intermediates corresponded to 44% of these chemicals, and herbicides and fungicides were more frequently associated to this hepatic injury.…”
Section: Discussionmentioning
confidence: 99%